2019
DOI: 10.1002/cncr.32291
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity screening: A missing piece in cancer management

Abstract: INTRODUCTIONFood insecurity remains an underrecognized social determinant of health. 1-3 In 2017, approximately 11.8% of US households were food insecure. These households included approximately 40 million individuals. 4 The percentage of foodinsecure households is higher among racial/ethnic minorities, single-parent and low-income households, and individuals with low levels of education. 4 Research establishing the relationships between food insecurity and many adverse health outcomes, including chronic condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 68 publications
1
44
0
Order By: Relevance
“…recruiting people with physical and mental health issues, those who had conditions that typically required dietary modification and monitoring for optimum management, and those who did not, and succeeded in gaining the diversity of experiences we hope to achieve. However, we did not speak to anyone who disclosed a cancer diagnosis and this is an important and potentially overlooked issue as the association between food insecurity and cancer outcomes remains poorly understood (38). Thirdly, we relied on participants' self-reported diagnosis and disclosure to make judgments about our sampling strategy and recruitment.…”
Section: Study Limitations and Strengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…recruiting people with physical and mental health issues, those who had conditions that typically required dietary modification and monitoring for optimum management, and those who did not, and succeeded in gaining the diversity of experiences we hope to achieve. However, we did not speak to anyone who disclosed a cancer diagnosis and this is an important and potentially overlooked issue as the association between food insecurity and cancer outcomes remains poorly understood (38). Thirdly, we relied on participants' self-reported diagnosis and disclosure to make judgments about our sampling strategy and recruitment.…”
Section: Study Limitations and Strengthsmentioning
confidence: 99%
“…However the experience of food insecurity as a health care issue and its impacts on patients' health condition management endeavours, has received relatively little attention in the UK to date, which is in contrast to other high income countries where poverty and food insecurity, and long term condition prevalence are similarly high (13,14,19,21,(36)(37)(38)(39)(40). A recent study of Scottish-based health care professionals, by the lead author, found that most believed that some of their patients were affected by food insecurity and that it was impacting their ability to manage their health condition(s)(41).…”
Section: Introductionmentioning
confidence: 99%
“…recruiting people with physical and mental health issues, those who had conditions that typically required dietary modi cation and monitoring for optimum management, and those who did not, and succeeded in gaining the diversity of experiences we hope to achieve. However, we did not speak to anyone who disclosed a cancer diagnosis and this is an important and potentially overlooked issue as the association between food insecurity and cancer outcomes remains poorly understood [44]. Thirdly, we relied on participants' self-reported diagnosis and disclosure to make judgments about our sampling strategy and recruitment.…”
Section: Study Limitations and Strengthsmentioning
confidence: 99%
“…The experience of food insecurity as a health care issue, and its impacts on patients' health condition management endeavours, has received relatively little attention in the UK to date. This lack of attention is in contrast to other high-income countries where poverty and food insecurity, and long-term condition prevalence are similarly high [20,22,24,[41][42][43][44][45][46]. A recent study of Scottish-based health care professionals, by the lead author, found that most believed that some of their patients were affected by food insecurity and that it was impacting their ability to manage their health condition(s) [47].…”
Section: Introductionmentioning
confidence: 99%
“…The experience of food insecurity as a health care issue, and its impacts on patients' health condition management endeavours, has received relatively little attention in the UK to date. This lack of attention is in contrast to other high-income countries where poverty and food insecurity, and long-term condition prevalence are similarly high [21,23,25,[43][44][45][46][47][48]. A recent study of Scottish-based health care professionals, by the lead author, found that most believed that some of their patients were affected by food insecurity and that it was impacting their ability to manage their health condition(s) [49].…”
Section: Introductionmentioning
confidence: 99%